Program Evaluation of a Distance Master's Degree Dental Hygiene Program: A Program Effectiveness Study. - Sensabaugh, Cynthia F.; Mitchell, Tanya Villalpando; Overman, Pamela R.; Van Ness, Christopher J.; Gadbury-Amyot, Cynthia C. (Journal of Dental Hygiene, 2016)
Purpose: The purpose of this study was to conduct a program evaluation of the University of Missouri-Kansas City Master of Science in Dental Hygiene Education Program (MSDH). This evaluation examined long-term outcomes in the context of stakeholders (the profession, the student, and the degree-granting institution). Methods: A mixed-methods approach was used to gather data from the 28 graduates from the MSDH program. An electronic questionnaire included both open- and closed-ended questions including demographic and practice data, and data related to alumni preparedness to reach their career goals. Virtual focus groups provided valuable insight into whether the program has achieved its goals, and prepared the graduates to meet their program competencies and future goals. Results: Out of a total of 28 individuals who have successfully completed the distance program (2001-2011), 19 participated in an online survey (67.8%). The majority of the participants (73.7%) participated in one of 3 focus groups. Sixty-three percent of the graduates are currently employed in dental hygiene education. Eighty-four percent of the respondents have published their research conducted while in the program, thereby contributing to the dental hygiene body of knowledge. Sixty-eight percent indicated that had the distance option not existed, they would not have been able to obtain their advanced degree in dental hygiene. Twenty-one percent of the respondents report either being currently enrolled in a doctoral program, or having completed a doctoral degree. Conclusion: These results suggest that the University of Missouri-Kansas City Master of Science in Dental Hygiene Education Program is meeting its goals from the perspective of all stakeholders and providing its graduates with access to education and educational resources to meet the program competencies and ultimately achieve their career goals.